2011
DOI: 10.1007/s00449-011-0556-5
|View full text |Cite
|
Sign up to set email alerts
|

Partial nitrification and nutrient removal in intermittently aerated sequencing batch reactors treating separated digestate liquid after anaerobic digestion of pig manure

Abstract: The performance of an intermittently aerated sequencing batch reactor (IASBR) technology was investigated in achieving partial nitrification, organic matter removal and nitrogen removal from separated digestate liquid after anaerobic digestion of pig manure. The wastewater had chemical oxygen demand (COD) concentrations of 11,540 ± 860 mg/L, 5-day biochemical oxygen demand (BOD(5)) concentrations of 2,900 ± 200 mg/L and total nitrogen (TN) concentrations of 4,041 ± 59 mg/L, with low COD:N ratios (2.9) and BOD(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 21 publications
5
25
1
Order By: Relevance
“…These results indicate that high DO concentration favors conditions for niftrifier bacteria to oxidize the ammonium and improve the removal percentages of TN and NH 4 + -N. However, decreasing aeration rate caused high dissolved organic carbon concentrations, which inhibited nitrification both in the anoxic and oxic zones and thereby increased the concentration of nitrogen in the effluent. Similar results were reported by [3], [22], [23].…”
Section: Effect Of Aeration Rate On Simultaneous Nitrification and Desupporting
confidence: 91%
See 2 more Smart Citations
“…These results indicate that high DO concentration favors conditions for niftrifier bacteria to oxidize the ammonium and improve the removal percentages of TN and NH 4 + -N. However, decreasing aeration rate caused high dissolved organic carbon concentrations, which inhibited nitrification both in the anoxic and oxic zones and thereby increased the concentration of nitrogen in the effluent. Similar results were reported by [3], [22], [23].…”
Section: Effect Of Aeration Rate On Simultaneous Nitrification and Desupporting
confidence: 91%
“…Similar results were reported by [3], [15], [16]. Therefore, it is suggested that Johkasou system is recommended to applied continuous oxygen supply at high rate to achieve simultaneously nitrification.…”
Section: Removal Of Organic Carbon and Nitrogen By Decreasing Aeratiosupporting
confidence: 85%
See 1 more Smart Citation
“…In recent years, most swine pollution treatment focuses on COD and NH 4 + -N removal [31]. However, P is also an important factor for swine wastewater that relates to water environment security.…”
Section: Phosphorus Estimationmentioning
confidence: 99%
“…High ammonium (NH 4 + -N) wastewater (including animal production wastewater, landfill leachate, and anaerobic digestate of waste sludge) has harmful effects on bodies of water and aquatic plants without proper treatment, which has been widely studied with regard to biological nitrogen removal (BNR) (Zhang et al 2007;Zhang et al 2011;Guo et al 2010). Shortcut nitrification and denitrification (SND) and anaerobic ammonium oxidation (Anammox) are two BNR processes suitable for the treatment of high ammonium wastewater.…”
Section: Introductionmentioning
confidence: 99%